THE IMPORTANCE OF IMPLEMENTING EMKM-BASED FINANCIAL ACCOUNTING STANDARDS (SAK) ON THE PREPARATION OF FINANCIAL STATEMENTS IN SHOP BUSINESSES IN SUKARAME DISTRICT, PALEMBANG - Hesi Septianti Amalia; Lukita Tripermata; Andini Utari Putri (Transpublika Publisher, 2023)
This study aims to determine whether the application of financial accounting standards by shop owners in Sukarame District is in accordance with the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM). The research method used is quantitative. The sample size for this study was 103 shopkeepers who operate businesses such as grocery stores, clothing stores, and clothing stores located in Sukarame District. Purposive sampling techniques were used with certain criteria. The data needed is primary data, collected through distributing questionnaires to shop business actors in Sukarame District. Based on the results of the study, it can be concluded that the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) have not been fully implemented in the financial statements of SME shops in Sukarame District. MSMEs only prepare simple reports such as profit and loss statements. This is because MSME shops around Sukarame District do not know about the existence of Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM). They have never even heard of what SAK EMKM is. This is due to the lack of knowledge of business actors and the low level of government socialization of the preparation of financial statements for SMEs.